Integrated Halal Infrastructure for Strengthening Indonesia’s Sharia Economic Ecosystem: Infrastruktur Halal Terintegrasi untuk Memperkuat Ekosistem Ekonomi Syariah Indonesia - Achmad Riady; Arif Mashuri; Siradjuddin, Siradjuddin (DIRASAH: Jurnal Kajian Islam, 2026)
Indonesia’s growing role in the global halal economy highlights the necessity of a well-developed halal infrastructure that ensures product integrity, strengthens consumer trust, and enhances industry competitiveness. However, existing studies and national practices tend to focus on isolated elements such as certification or logistics, resulting in fragmented implementation and uneven institutional capacity across regions. This study aims to provide an integrated analysis of halal infrastructure covering certification governance, halal laboratory networks, halal logistics, and digital traceability systems and examine how these components collectively reinforce the Sharia economic ecosystem in Indonesia. Using a qualitative literature review supported by policy reports and empirical case documentation, the study synthesizes Institutional Theory, the Resource-Based View, and the maqāṣid al-sharī‘ah framework to analyze structural, operational, and ethical dimensions. The findings show that coordinated institutional arrangements, capacity development of laboratories, and digital integration significantly enhance efficiency and credibility, although disparities remain in regional access and SME readiness. The study concludes that holistic infrastructure development is essential for sustainable and inclusive Sharia economic growth, contributing a conceptual framework to guide future policy and empirical research.